The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ppa.13169
|View full text |Cite
|
Sign up to set email alerts
|

Nickel potentiates soybean resistance against infection by Phakopsora pachyrhizi

Abstract: Asian soybean rust (ASR), caused by the fungus Phakopsora pachyrhizi, causes significant yield losses worldwide. Nickel (Ni) plays a key role in the metabolism of some profitable crops, such as soybeans, because it is a constituent of several biomolecules and is required for the catalytic process of several enzymes. This study investigated the effect of foliar Ni treatment on the potentiation of soybean cultivar TMG 135 resistance to P. pachyrhizi infection at the microscopic, biochemical, and molecular levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
1
26
0
2
Order By: Relevance
“…In this study, we report the effects of Gl and additional foliar Ni application on soybean resistance against P. pachyrhizi infection. Earlier reports demonstrated that Gl and Ni application decreased ASR development on soybean plants (Feng et al 2005, 2008, Einhardt et al 2020). The results of this study corroborate those reports and provide novel evidence of an additional effect of the combination of Ni and Gl on the maintenance of the photosynthetic capacity of infected plants.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In this study, we report the effects of Gl and additional foliar Ni application on soybean resistance against P. pachyrhizi infection. Earlier reports demonstrated that Gl and Ni application decreased ASR development on soybean plants (Feng et al 2005, 2008, Einhardt et al 2020). The results of this study corroborate those reports and provide novel evidence of an additional effect of the combination of Ni and Gl on the maintenance of the photosynthetic capacity of infected plants.…”
Section: Discussionmentioning
confidence: 92%
“…Plants (V4 growth stage and with three fully expanded leaves) were sprayed with a solution (7.2 ml per plant; pH 6.0) of 0.19 g l −1 NiSO 4 .6H 2 O. This dose was used based on the study carried out by Einhardt et al (2020). At 24 h after Ni spray, plants were sprayed with Roundup Original® (Monsanto) (7.2 ml per plant of a solution of 0.667 g l −1 of acid equivalent of N‐(phosphonomethyl) glycine (Gl); equivalent to 960 g ha −1 a.e.).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations